Comparative study of various intra ocular lens formulae by IOL master - Kishore, Arikeri Krishna; Kavitha, Kuruva Nandyala Sree; Ratnam, Peram Venkata; Raman, Yenugandula; Krishna, Balaka Bala; Keerthi, Murahari Vijaya (International Journal of Research in Medical Sciences, 2017)
Background: The aim and objective of the study was to calculate intraocular lens power with IOL master in 100 eyes of 100 patients with long axial lengths between 25mm to 32mm.To analyse and compare the results of various formulae by postoperative auto refractometry and corrected distance visual acuity and to know the most accurate formula for highly myopic eyes (Axial length more than 25.00 mm). Methods: Patients coming to Sarojini Devi Eye Hospital from December 2012-September 2014 for cataract surgery were considered in this study. All patients with visually significant cataract having fundus findings within normal limits were included in this study and patients of complicated cataract due to trauma, uveitis, Glaucoma and any corneal pathology were excluded from the study. Results: The Mean AL was 27.25 ± 1.25 mm, the Mean keratometric value was 43.62 ± 1.45 D, and the Mean Absolute Error (MAE) calculated by the Haigis was 0.07 DD. Compared to the MAEs generated by the other formulae, the MAE generated by the Haigis was comparable to that by the SRK/T (0.231 D), and significantly lower than those by the Hoffer Q (0.481 D) and Holladay (0.864 D). Conclusions: The Mean post-operative refractive error (spherical equivalent) was found to be the least with Haigis formula followed by SRK/T for eyes with long axial length. The HAIGIS formula has a better predictability and accuracy. The postoperative hyperopic shift was comparable between HAIGIS and SRK-T formulae the least postoperative hyperopic shift with Haigis formula compared to other formulae.